A replacement of chromate coating for adhesive bonding of stainless steel in a corrosive environment - Alawadhi, Khaled; Brown, Richard; Alsarraf, Jalal (International Journal of Engineering and Technology, 2014)
For adhesive bonding of stainless steel to itself, a surface treatment involving chromates is used. However, chromates are environmentally unfriendly so a replacement is being sought. In this paper, an alternative to chromate was investigated. The standard test method, ASTM D 1002, was used to measure the failure load of adhesively bonded stainless steel samples. A general-purpose epoxy adhesive was used. To simulate marine exposure, adhesively bonded samples were placed in a 5% salt spray for extended periods of time, up to five weeks. Results indicated that the initial shear strength of adhesive joints prepared with a traditional chromate preparation was 25% greater than the new, alternative coating. However, more importantly, the rate of decrease in strength with salt spray exposure was greater for the chromate than for the alternative. After 21 days, both bonding surface treatments had the same strength. However, after this period of time, the alternative was stronger than the chromate treatment, indicating that the alternative was a more durable coating. An adhesive/adherent coated system was investigated using a finite element method in order to investigate the influence of adhesive thickness between the adhesive and the adherent, and the residual stress in the adhesive layer. Keywords: Adhesive, Alternative Coating, Crevice Corrosion, Potentio-Dynamic, Salt Spray.